Acute right heart failure in Waldenström macroglobulinemia: A case report - Memis Hayat; Balinisteanu Anca Elena; Gaman Mihaela; Mihalcea Diana; Vinereanu Dragos (Sciendo, 2022)
Waldenström macroglobulinemia (WM) is a low-grade B-cell clonal disorder with lymphoplasmacytic bone marrow involvement and monoclonal immunoglobulin M (IgM) with poor prognosis. Clinical features include anemia, thrombocytopenia, hepatosplenomegaly, lymphadenopathy and hyperviscosity. We report the case of a 42-year-old male who presented with unexplained weight loss. The diagnosis of WM was established after morphological and immunohistochemical examination of the patient's bone marrow along with an elevated serum IgM level. He started chemotherapy with cyclophosphamide, bortezomib, dexamethasone and, four months later, rituximab was added. Five months later the patient presented with relapse of the hematological disease, hyperviscosity syndrome and acute right heart failure. Echocardiography showed a dilated right ventricle with decreased global systolic function and severe systolic pulmonary artery pressure, with normal left cardiac function and volumes. Despite maximal medical therapy, the patient died in day six of hospitalization. This case is distinguished by the rapidly evolving rare haematological cancer despite optimal chemotherapy and a multidisciplinary approach associated with chemotherapy-related late right heart dysfunction in a young man, without any cardiovascular risk factors or previous myocardial disease.